Baricitinib in severe and refractory peripheral ulcerative keratitis: a case report and literature review. (November 2022) - Calvo-Río, Vanesa; Sánchez-Bilbao, Lara; Álvarez-Reguera, Carmen; Castañeda, Santos; González-Mazón, Iñigo; Demetrio-Pablo, Rosalía; González-Gay, Miguel A.; Blanco, Ricardo
Ocular disease, such as scleritis and peripheral ulcerative keratitis (PUK), may be a serious ocular complication. We present a patient with severe and refractory PUK treated with baricitinib. A review of the literature on Janus kinase inhibitors (JAKINIB) in refractory ocular surface pathology was also performed. For the literature review, the search in PubMed, Embase, and the Cochrane library was carried out from inception until 31 May 2021, including conference proceedings from four major rheumatology congresses. All original research articles studying JAKINIB treatment in patients with inflammatory eye disease were included. We present an 85-year-old woman with rheumatoid arthritis (RA) and secondary Sjögren's syndrome refractory to methotrexate, leflunomide, certolizumab pegol, adalimumab, and tocilizumab (TCZ). However, 10 months after starting TCZ, the patient suffered a perforation secondary to PUK, requiring urgent surgical intervention. In the absence of infection, she was treated with boluses of intravenous methylprednisolone followed by oral prednisone at high doses in a decreasing pattern together with baricitinib at a dose of 2 mg/day with a very rapid and persistent favorable response to eye and joint symptoms. After 18 months of treatment, the patient had not presented serious side effects or signs of reactivation of her disease. In addition to this report, three other studies including one PUK associated with RA and two non-infectious scleritis treated with tofacitinib were included in this literature review. All three patients had experienced an insufficient response to conventional treatment, including biologic agents, before being switched to JAKINIB, leading to a complete or partial recovery in all of them without significant adverse effects so far. JAKINIBs (baricitinib and tofacitinib) may be an effective and safe therapy in patients with severe autoimmune and refractory ocular surface pathology, such as scleritis and PUK.